Evaluation of Activity Limitation in Patients With Idiopathic Pulmonary Fibrosis Grouped According to Medical Research Council Dyspnea Grade - Kozu, Ryo; Jenkins, Sue; Senjyu, Hideaki (Archives of physical medicine and rehabilitation, 2014)
To investigate the relations between Medical Research Council (MRC) dyspnea grade and peripheral muscle force, activities of daily living (ADL) performance, health status, lung function, and exercise capacity in subjects with idiopathic pulmonary fibrosis (IPF). Prospective cross-sectional observational study. University hospital. Subjects with IPF (N=65, 46 men) in a stable clinical state with a mean age of 68±7 years. Not applicable. Right ventricular systolic pressure (RVSP) via transthoracic echocardiography, pulmonary function, isometric quadriceps force (QF) and handgrip force (HF), 6-minute walk distance (6MWD), ADL score, and health status (Medical Outcomes Study 36-Item Short-Form Health Survey [SF-36]) were assessed and compared between subjects grouped according to MRC grade. Of the participants, 16 were in MRC grade 2, 17 were in MRC grade 3, 17 were in MRC grade 4, and 15 were in MRC grade 5. RVSP, pulmonary function, QF, HF, 6MWD, ADL, and SF-36 scores decreased with increasing MRC grade (all P<.001). All measures were lower (P<.05) in subjects with grades 4 and 5 than subjects with grades 2 and 3. Strong associations were found between MRC grade and 6MWD (ρ=−.89, P=.001) and ADL score (ρ=−.82, P=.001). MRC grade was also associated with RVSP, pulmonary function, QF, and HF (all ρ≥.56, P=.001). The MRC dyspnea scale provides a simple and useful method of categorizing individuals with IPF with respect to their activity limitation and may assist in understanding the impact of IPF on an individual.